The effect of cooperative learning on improving college students' reading comprehension (2013)
One of the major challenges for learners and instructors is to find the way of improving reading comprehension achievements. Fortunately, cooperative learning is a method through which this can be implemented and improved, since it encourages students to work in small team groups with different level of ability, where they help each other, they are responsible for their learning as well as the teammates learning, and work on an assignment until all member successfully understand and complete it. Also, this method permit students to acquire more language and social skills that others whom studying the same content under individualistic classroom condition will never reach. Beside, it maximize opportunities for authentic and communicate language, it enriches the language, the interaction among companions and it increase opportunity to individualize instruction.